(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Solar energy is becoming an important source of sustainable and environmentally friendly energy in the modern world. Solar panels have become one of the main directions in the energy supply for sunny countries. However, the energy efficiency of solar panels is still limited, and continuous research is being conducted in this area to increase efficiency. The method of introducing impurities (doping) into semiconductor materials allows you to significantly increase the efficiency of solar panels. This article provides information on the principle of operation of solar panels, the importance of introducing impurities.